2016
DOI: 10.1037/tps0000055
|View full text |Cite
|
Sign up to set email alerts
|

Positive emotions elicited by clowns and nurses: An experimental study in a hospital setting.

Abstract: The present research is first to investigate the unique effect of a humorous clown intervention on patients' emotional state in comparison with a different kind of intervention in a hospital setting using a controlled experimental method. Forty-four adult patients of a physical rehabilitation center were randomly assigned to either participate or observe 2 interventions: a hospital clown and a nurse intervention. Compared with baseline and the nurse intervention, the clown intervention elicited a higher level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Hospital clown interventions apparently elicit feelings that go beyond the typical humor response, such as feelings of connection, liberation, appreciation or playfulness. In this sense, the present research validates studies using self-report measures ( Auerbach et al, 2014 , 2016 ), and strengthens the widespread assumption of practitioners and clown organizations (see Dionigi et al, 2012 ) that on average hospital clown interventions successfully create positive experiences and emotions for patients in need of care.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Hospital clown interventions apparently elicit feelings that go beyond the typical humor response, such as feelings of connection, liberation, appreciation or playfulness. In this sense, the present research validates studies using self-report measures ( Auerbach et al, 2014 , 2016 ), and strengthens the widespread assumption of practitioners and clown organizations (see Dionigi et al, 2012 ) that on average hospital clown interventions successfully create positive experiences and emotions for patients in need of care.…”
Section: Discussionsupporting
confidence: 85%
“…Participants rate their current state on a 7-point Likert scale ranging from 1 (=not at all) to 7 (=very strongly). As the sample size in the present study is too small to test the hypotheses with all single ratings, factor scores were used instead (transcendence, uneasiness, amusement, and arousal; the procedure is described in detail in Auerbach et al, 2016 ), which are sensitive enough to capture changes in clown-induced emotional states ( Auerbach et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, humor-based PPIs are expected to be well-received by the participants and enable a higher commitment to continue practicing and incorporating the activities into daily life. It has been shown that humor induces amusement ( Ruch, 2001 , 2008 , 2009 ; Auerbach et al, 2016 ), an important facet of positive emotions (the one that most frequently goes along with laughter; Platt et al, 2013 ). Given that the elicitation of positive emotions is one of the proposed working mechanisms of PPIs ( Sin and Lyubomirsky, 2009 ), humor seems to be particularly well-suited for incorporation in PPIs.…”
Section: Introductionmentioning
confidence: 99%